Analisis Dampak Harga Gabah Terhadap Kesejahteraan Petani Padi Sawah di Desa Buttu Sawe Kecamatan Duampanua Kabupaten Pinrang - Rahman Rahman; Andi Nuddin; Andi Erna Sriwahyuningsih (Universitas Muslim Maros, 2023)
Buttu Sawe Village is one of the villages in Duampanua District, Pinrang Regency, where most of the area is agricultural land. The people in this village carry out agricultural business because from a geographical point of view the area still has a lot of agricultural land. The average ownership of agricultural land by rice farmers in Buttu Sawe Village is less than